Trends in banking efficiency and returns to scale: Evidence from ASEAN-6 banking sectors - Shukur, Nabilah Abdul; Sufian, Fadzlan (Journal of Islamic, Social, Economics and Development, 2025)
The present study examines the efficiency and returns to scale of the banking sectors in the six most prominent ASEAN economies. The empirical analysis covers the period from 2013 to 2021, capturing both the pre-pandemic years and the peak of the COVID-19 crisis. The results indicate that the banking sectors of the middle-income countries exhibit higher efficiency levels in comparison to the high- and low-income countries banking sectors. The empirical findings also indicate that the banking sectors of the ASEAN-6 most prominent economies have been adversely affected by the COVID-19 pandemic crisis. We find that most banks have been functioning at the "suboptimal” scale of operations. These banks could either be proportionately smaller or disproportionately larger than ideal. This study also highlights significant policy implications and the necessity of enhancing economic efficiency and stability in the ASEAN-6 banking sectors through effective resource allocation, technology-driven financial services, and regulatory reforms. It recommends embracing best practices from middle-income countries, fostering mergers and acquisitions, digital transformation, and developing customized strategies to cater to the distinct needs of each income group.